2019
DOI: 10.1038/s41598-019-56461-4
|View full text |Cite
|
Sign up to set email alerts
|

9-ING-41, a small molecule inhibitor of GSK-3beta, potentiates the effects of anticancer therapeutics in bladder cancer

Abstract: Glycogen synthase kinase-3 beta (GSK-3β), a serine/threonine kinase, has been identified as a potential therapeutic target in human bladder cancer. In the present study, we investigated the antitumor effect of a small molecule GSK-3β inhibitor, 9-ING-41, currently in clinical studies in patients with advanced cancer, in bladder cancer cell lines. We found that treatment with 9-ING-41 leads to cell cycle arrest, autophagy and apoptosis in bladder cancer cells. The autophagy inhibitor chloroquine potentiated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Our results point to the effects that both WT-GSK-3β and KD-GSK-3β can have on sensitivity of certain pancreatic and breast cancer cells to chemotherapy and targeted therapy. These results are important as chemotherapeutic drugs can alter the activity of GSK-3β [3,86]. Therefore, without knowing the downstream consequences, suppression or activation of GSK-3β may change the sensitivity to targeted therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Our results point to the effects that both WT-GSK-3β and KD-GSK-3β can have on sensitivity of certain pancreatic and breast cancer cells to chemotherapy and targeted therapy. These results are important as chemotherapeutic drugs can alter the activity of GSK-3β [3,86]. Therefore, without knowing the downstream consequences, suppression or activation of GSK-3β may change the sensitivity to targeted therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…The protective autophagy-inducing properties of 9-ING-41 were demonstrated in bladder cancer cells by Kuroki et al. 55 They pointed out that combined treatments with 9-ING-41 and CQ enhanced the toxic effect of 9-ING-41 on bladder cancer cells. They further reported that in chemo-resistant T24 and HT1376 bladder cancer cell lines, 9-ING-41 increased the anti-tumor effect of cisplatin and GC.…”
Section: Survival Effects Of Autophagy On Bladder Cancer Cellsmentioning
confidence: 98%
“…9-ING-41, for instance, is a malmeimide-derived GSK3 inhibitor that initially showed potent anti-proliferative activity [203] and capacity to overcome chemoresistance [204] in different cancer cell lines. At the moment, the safety and efficacy of 9-ING-41 are being addressed in patients with hematologic malignancies and solid tumors in a phase I/II study (NCT03678883) [197,205].…”
Section: Clinical Application Of Gsk3 Inhibitorsmentioning
confidence: 99%